Comparative experimental study of myocardial protection with crystalloid solutions for heart transplantation - Lima,Melchior Luiz (2012)
BACKGROUND: There is a growing need to improve myocardial protection, which will lead to better performance of cardiac operations and reduce morbidity and mortality. Therefore, the objective of this study was to compare the efficacy of myocardial protection solution using both intracellular and extracellular crystalloid type regarding the performance of the electrical conduction system, left ventricular contractility and edema, after being subjected to ischemic arrest and reperfusion. METHODS: Hearts isolated from male Wistar (n=32) rats were prepared using Langendorff method and randomly divided equally into four groups according the cardioprotective solutions used Krebs-Henseleit-Buffer (KHB), Bretschneider-HTK (HTK), St. Thomas-1 (STH-1) and Celsior (CEL). After stabilization with KHB at 37ºC, baseline values (control) were collected for heart rate (HR), left ventricle systolic pressure (LVSP), maximum first derivate of rise left ventricular pressure (+dP/dt), maximum first derivate of fall left ventricular pressure (-dP/dt) and coronary flow (CF). The hearts were then perfused at 10ºC for 5 min and kept for 2 h in static ischemia at 20ºC in each cardioprotective solution. Data evaluation was done using analysis of variance in completely randomized One-Way ANOVA and Tukey's test for multiple comparisons. The level of statistical significance chosen was P<0.05. RESULTS: HR was restored with all the solutions used. The evaluation of left ventricular contractility (LVSP, +dP/ dt and -dP/dt) showed that treatment with CEL solution was better compared to other solutions. When analyzing the CF, the HTK solution showed better protection against edema. CONCLUSION: Despite the cardioprotective crystalloid solutions studied are not fully able to suppress the deleterious effects of ischemia and reperfusion in the rat heart, the CEL solution had significantly higher results followed by HTK>KHB>STH-1.